Hayek and complexity: coordination, evolution and methodology in social adaptive systems - Cunha, Gabriel Oliva Costa (2016)
The affinity between the work of the Austrian economist Friedrich A. Hayek and the approach of Complexity Economics is widely recognized by the literature. In spite of this, there still is a lack of studies that seek to analyze in depth the relationship between Hayek and complexity. This dissertation is a contribution to the filling of this large gap in the literature. In the first part of the work, we analyze the various periods in the development of Hayek\'s vision of complexity, showing that this vision is strongly present in his works on knowledge, competition, methodology, evolution, and spontaneous order. In the second part, we explore how Hayek was influenced by two of the main precursors of modern complexity theory - cybernetics and general system theory - from the time he was working on his book on theoretical psychology, The Sensory Order (1952), until the end of his intellectual career.